2021
DOI: 10.1093/gerona/glab268
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Mobility Determinants and Life Space Among Older Adults

Abstract: Background It is important to understand the factors associated with life space mobility so that mobility disability can be prevented/treated. The purpose of this study was to identify the association between mobility determinants and life space among older adults. Methods This study was a cross-sectional analysis of 249 community-dwelling older adults (mean age=77.4 years, 65.5% female, 88% white) who were recruited for a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Future research should examine the factors associated with app-based navigation walks in combination with an assessment of higher brain function. Regarding LSA, De Silva et al (2019) showed that cognitive decline in older adults with limited living space, and Dunlap et al (2021) found a significant relationship between LSA scores and gait-related measures. Considering the relationship between walking speed, cognitive function and LSA, efficient app-based navigation and life space may also have a bidirectional relationship.…”
Section: Discussionmentioning
confidence: 98%
“…Future research should examine the factors associated with app-based navigation walks in combination with an assessment of higher brain function. Regarding LSA, De Silva et al (2019) showed that cognitive decline in older adults with limited living space, and Dunlap et al (2021) found a significant relationship between LSA scores and gait-related measures. Considering the relationship between walking speed, cognitive function and LSA, efficient app-based navigation and life space may also have a bidirectional relationship.…”
Section: Discussionmentioning
confidence: 98%
“…This may suggest that they have more physical reserves and are thus willing to travel further to a specific type of destination. Previous studies have shown that mobility restrictions are associated with a smaller activity range (Iveson et al 2023 ) and lower life-space mobility (Dunlap et al 2022 ), indicating that older adults with mobility limitations may have more limited use of their environment (Iveson et al 2023 ). The physical exercise and attractive destinations reported by those with walking difficulty were all within one kilometer from home.…”
Section: Discussionmentioning
confidence: 99%
“…Life-space mobility refers to the spatial area in which a person moves in daily life, taking into account distance, frequency, and any assistance needed for movement. Restrictions in participating in out-of-home activities are known to correlate, for example, with functional limitations, pain, depression, and chronic conditions [ 11 - 13 ]. Previously it has also been shown that life-space mobility correlates with, for example, quality of life [ 14 , 15 ], physical functioning, and autonomy [ 16 ], and that restrictions on it may lead to cognitive decline [ 17 , 18 ], falls and fractures [ 19 ], nursing home admission [ 20 ], or even mortality [ 21 ].…”
Section: Introductionmentioning
confidence: 99%